Clinical Outcomes of Patients Treated for Candida auris Infections in a Multisite Health System, Illinois, USA - Arensman, Kellie (Emerg Infect Dis, 2020)
Candida auris is an emerging fungal pathogen that is typically resistant to fluconazole and is known to cause healthcare-associated outbreaks. We retrospectively reviewed 28 patients who had >1 positive culture for C. auris within a multisite health system in Illinois, USA, during May 2018–April 2019. Twelve of these patients were treated as inpatients for C. auris infections; 10 (83%) met criteria for clinical success, defined as absence of all-cause mortality, C. auris recurrence, and infection-related readmission at 30 days from the first positive culture. The other 2 patients (17%) died within 30 days. Most patients (92%) were empirically treated with micafungin. Four (14%) of 28 total isolates were resistant to fluconazole, 1 (3.6%) was resistant to amphotericin B, and 1 (3.6%) was resistant to echinocandins. Our findings describe low rates of antifungal resistance and favorable clinical outcomes for most C. auris patients.